The Influence of Parental Role on Adolescent Sexual Behaviour and HIV/AIDS in KwaZulu-Natal, South Africa. - Ringisai, Lovemore (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2024)
Background: HIV/AIDS risky behaviour remains a critical health concern for adolescents, specifically at high school level. In South Africa, the rapid increase of risky lifestyles and sexual behaviours among adolescents could be mainly attributed to poor parental skills and broken family structures. Four identified sexual risk behaviours that are of concern in South Africa are age at sexual debut, multiple sexual partners, condom use and transactional sex.Methods: Data was collected using a quantitative cross-sectional survey with samle consist with 450 male and female high school adolescents between 14 to 18 years from 3 different South African school settings. Collected data was analyzed using SPSS descriptive statistics procedure.Result: 79.7% of the respondents had only one parent still alive with 4.9 % of the respondents indicated to have lost both parents. Only 13.5% of the respondents were from a nuclear family. The majority of the respondents were (41.2%) living with grandparents. This high level of family disintegration, parental absence and poor parenting skills in South Africa exposed 73.3% (330) of the respondents to early sexual debut, transactional sex, unprotected sex and having multiple sexual partners. The study proved that there is a statistical association between guardianship and age at sexual debut; guardianship and multiple sexual partners; guardianship and condom use; guardianship and transactional sex.Conclusion : The revealed significant high risk sexual behaviour among adolescents in KwaZulu-Natal should inform Health and educational authorities to utilize these key findings to design more effective local strategies to train and assist parents and caregivers on parenting skills